Inmates with Severe Mental Disorders: A Challenge for the Prison System - Popa, Ecaterina; Iurchevici, Iulia (New Trends in Psychology, 2025)
This article explores the pressing issue of inmates with severe mental disorders, a group that is both highly vulnerable and particularly challenging to manage within the prison system. Drawing on specialized literature and institutional reports, it examines the clinical and behavioral profiles of these individuals, the major difficulties posed by the prison environment, and the resulting implications for security and mental health. Special consideration is given to inmates diagnosed with schizophrenia—one of the most common psychiatric conditions in correctional facilities—which raises complex treatment and reintegration challenges. Building on international research and exploratory data, the article formulates a set of practical recommendations, including the creation of specialized units, closer collaboration between prisons and psychiatric hospitals, targeted staff training, and the implementation of psychosocial programs. The conclusions stress the urgent need for a comprehensive public policy that balances security requirements with mental health needs, safeguards fundamental rights, reduces recidivism risk, and promotes the effective social reintegration of inmates with severe mental disorders.